Critical literacy, literature and initial training of teachers in the 1st cycle of basic education for the construction of critical citizenship. - Gamboa, Maria José (Aprender, 2023)
The new ways of being, thinking and participating in contemporaneous societies encourage us to reflect on the role of linguistic education in general and literary education in particular in order to build the world we want to live in, and challenge us to rethink the initial training of future teachers.Therefore, within the scope of this article, the aim is to provide data from an exploratory study, of a qualitative nature, carried out within the scope of the training of professional master's students, future teachers in the first years of schooling in portuguese basic education, regarding their perceptions on the relevance of critical literacy, with literature, in the first years of formal schooling and the respective pedagogical ways of constructing it.Through problematization and didactic intervention exercises, carried out in the context of a Portuguese Didactics class, it was possible to understand and problematize perceptions of critical literacy and ways of approaching it in early childhood education, in order to help students reflect on the potential of a critical pedagogy of literacy.The data challenge and support the relevance of thinking about the initial training of teachers at initial levels of education, considering literacy models that enhance a pedagogy of critical literacy.
Keywords: critical literacy, literature, teacher trainning; teacher training